Triagem antimicrobiana de extratos vegetais frente a isolados ambientais de Staphylococcus aureus Oxacilina resistentes (ORSA) - Silva, Jeferson Júnior Da (2013)
Currently S. aureus methicillin resistant (MRSA) is the most important nosocomial pathogen due to multidrug resistance to available antimicrobials, which directs efforts in the search for new therapies. In this study we evaluated the in vitro antimicrobial activity of plant extracts against ambient aerial isolates of MRSA previously identified. The hydroethanolic extracts of Annona crassiflora, Bidens pilosa, Eugenia pyriformis, Heliconia rostrata and Plinia cauliflora were obtained by steeping in ethyl alcohol, 70%, evaporated and lyophilized. The antimicrobial activity was evaluated by agar diffusion and determination of minimum inhibitory concentration (MIC) by microdilution broth. Toxicity testing in cell culture and phytochemical analysis complemented the analysis where most of the extracts showed low toxicity, presence of alkaloids, flavonoids, tannins and saponins. The extracts of leaf, stem and fruit rind of Plinia cauliflora, stem and leaf of Eugenia pyriformis, stem, pulp, fruit rind and leaf of Annona crassiflora and flower, stem and leaf of Bidens pilosa were effective against multidrug-resistant samples analyzed being that the leaf extract of Bidens pilosa showed the best in vitro anti-MRSA activity by both methods evaluated.